STRATEGI KOMUNIKASI NEGOSIASI UNTUK MENINGKATKAN KESUKSESAN BISNIS - Arisma, Lusi Yuliana; Harmonis, Harmonis (Triwikrama: Jurnal Ilmu Sosial, 2024)
Communication needs in today's business competition continue to change. The negotiation process is the main thing in supporting the progress of a business. In the context of the communication process, the negotiator has a role as a communicator who initiates the communication process in negotiations. So communication skills are a determining factor in the success of every individual and organization to survive in today's highly competitive business competition. To find out the communication strategy used, this research examines it using data collection techniques through literature study. The main data sources used as material for this research are books, journals and internet sites related to the chosen topic. So it can be concluded that in a business context, establishing good relationships with business partners or potential business partners is an important key. This good relationship not only has an impact on the business aspect, but also has a positive psychological impact and contributes to a beneficial social impact. Keywords: Communication Strategy, Negotiation, Business Success.